1983
DOI: 10.1128/jb.154.1.383-386.1983
|View full text |Cite
|
Sign up to set email alerts
|

Locus of the Pseudomonas aeruginosa toxin A gene

Abstract: The gene for Pseudomonas aeruginosa toxin A has been mapped in the late region of the chromosome of strain PAO. Strain PAO-PR1, which produces parental levels of toxin A antigen that is enzymatically inactive and nontoxic, was used as the donor for R68.45 plasmid-mediated genetic exchange. Strain PAO-PR1 (toxA1) was mated with toxin A-producing strains, and exconjugates for selected prototrophic markers were tested for the transfer of toxA1. The toxA1 gene was located between cnu-9001 and pur-67 at approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…and 3083-2 chromosomes is his tox trp vct met (13,14), the CT structural genes are separated from tox by at least one gene that is not directly related to CT synthesis, i.e., trp. A similar observation has recently been reported for toxin A produced by many Pseudomonas aeruginosa isolates (4). The position of the toxin A structural gene on the P. aeruginosa PAO genetic map was found to be approximately 45 min away from a gene that apparently regulates production of toxin A.…”
supporting
confidence: 85%
“…and 3083-2 chromosomes is his tox trp vct met (13,14), the CT structural genes are separated from tox by at least one gene that is not directly related to CT synthesis, i.e., trp. A similar observation has recently been reported for toxin A produced by many Pseudomonas aeruginosa isolates (4). The position of the toxin A structural gene on the P. aeruginosa PAO genetic map was found to be approximately 45 min away from a gene that apparently regulates production of toxin A.…”
supporting
confidence: 85%
“…This study has demonstrated that the genes for regulation of formation and release of extracellular proteins in P. aeruginosa were located in different parts of the chromosome but not in the region of the chromosome in which the structural genes for elastase and exotoxin A were found (80'to-85' region [12,16]), There were indications of clustering of xcp genes in certain areas, such as 35' (xcp-2, xcp-31xcp-31); 40' (xcp4, xcp41-xcp45); and 55' (xcp-5, xcp-S1, xcp-52, xcp-53). Analysis of the phenotype properties of the strains showed that the mutations caused pleiotropic effects and revealed two distinct classes of mutants, tentatively designated class I and class II.…”
Section: Discussionmentioning
confidence: 90%
“…The tox-2 mutant produces 100-fold less toxin yet still maintains parental levels of protease and total extracellular protein. Since this tox-2 locus is well separated from the toxin structural gene of PA01 (toxA-1) at 85 min, as determined by Hanne et al (10), it has been suggested that the expression of the toxin-encoding gene is positively regulated by the gene product of the tox-2 locus. Gray et al (8) recently cloned the exotoxin A structural gene into Escherichia coli but expression of toxin could not be detected without placing the gene under the control of E. coli transcriptional/translational signals.…”
mentioning
confidence: 89%
“…Identical in mode of action to diphtheria toxin, exotoxin A catalyzes the transfer of the ADP-ribosyl moiety of NAD onto elongation factor 2, thereby inhibiting protein synthesis in eucaryotic cells (15,16). Exotoxin A is chromosomally encoded (10) and is produced by most (>90%) P. aeruginosa strains (4).…”
mentioning
confidence: 99%